Educación para los ciudadanos del siglo XXI: la educación colaborativa y emprendedora - Bautista Pizarro, Sisi (2013)
This article is a reflection on the characteristics that the author considersessential for the education of the XXI century citizens.The development of ideas begins by mentioning the fourth pillar ofeducation: “Learning to be” of Delors Report (1996), as substantialprecedent to address this issue. Then the author reflects about thecurrent need for collaborative and entrepreneurial education foraysinto the lives of learners-citizens of XXI century, as applications ofhuman freedom.